Analisa Yuridis Terhadap Korban Perampokan yang di Sertai dengan Kekerasan : ( Studi Kasus Perampokan di Kota Batam ) (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This study explores the juridical analysis of victims of robbery accompanied by violence. This research uses a qualitative approach. The results of the analysis show that the victims experienced significant psychological, physical and economic impacts, especially in the city of Batam. In the scarcity of laws in Indonesia, it is necessary to protect victims of robbery and violence based on laws and regulations that adhere to the rights of victims and the obligations of law enforcement. in providing effective protection to victims, including access to legal forms of rehabilitation and social tolerance. This journal provides insight for practical legal policy makers and law enforcement agencies in efforts to protect victims.